Direct top-quark width measurement at CDF - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2010)
We present a measurement of the top-quark width in the lepton+jets decay channel of tt̄ events produced in pp̄ collisions at Fermilab's Tevatron collider and collected by the CDF II detector. From a data sample corresponding to 4.3fb⊃-1 of integrated luminosity, we identify 756 candidate events. The top-quark mass and the mass of the hadronically decaying W boson that comes from the top-quark decay are reconstructed for each event and compared with templates of different top-quark widths (Γt) and deviations from nominal jet energy scale (ΔJES) to perform a simultaneous fit for both parameters, where ΔJES is used for the in situ calibration of the jet energy scale. By applying a Feldman-Cousins approach, we establish an upper limit at 95% confidence level (CL) of Γt<7.6GeV and a two-sided 68% CL interval of 0.3GeV<Γt<4.4GeV for a top-quark mass of 172.5GeV/c2, which are consistent with the standard model prediction. © 2010 The American Physical Society.